A Numerical Solution for the Heat Transfer in Non-Newtonian Flow Past Aa Wedge with Non-Isothermal Surface - Vasantha, R.; Pop, I.; Nath, G. (Engineering Transactions, 1988)
In this paper, we present results obtained by using a numerical method for calculating the development of the thermal boundary layer in a non-Newtonian flow past a wedge having a step discontinuity in surface temperature. In particular, solutions are determined for small values of the Prandtl number and the method is shown to be very accurate in comparison with previous analytical solutions.